2019
DOI: 10.1186/s13007-019-0436-6
|View full text |Cite
|
Sign up to set email alerts
|

A high-throughput delayed fluorescence method reveals underlying differences in the control of circadian rhythms in Triticum aestivum and Brassica napus

Abstract: Background A robust circadian clock has been implicated in plant resilience, resource-use efficiency, competitive growth and yield. A huge number of physiological processes are under circadian control in plants including: responses to biotic and abiotic stresses; flowering time; plant metabolism; and mineral uptake. Understanding how the clock functions in crops such as Triticum aestivum (bread wheat) and Brassica napus (oilseed rape) therefore… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(37 citation statements)
references
References 56 publications
3
34
0
Order By: Relevance
“…Interestingly, rhythms appeared to be most robust at 22°C, which might not be expected given that the warmest months in Sweden average around 15-17°C. A similar loss of rhythm robustness at lower temperatures has been observed in wheat(23).…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…Interestingly, rhythms appeared to be most robust at 22°C, which might not be expected given that the warmest months in Sweden average around 15-17°C. A similar loss of rhythm robustness at lower temperatures has been observed in wheat(23).…”
Section: Discussionsupporting
confidence: 79%
“…Six 96-well plates can be imaged simultaneously in each cabinet. Imaging conditions were exactly those described for constant light (L:L) imaging of Brassica leaves in Rees et al 2019(23). Images were captured every hour with a 1-minute exposure time.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Images were taken every 90 min for 6 d, with an exposure time of 20 min. Images were taken using a LUMO charge-coupled device camera (QImaging, Canada) controlled using Micro-Manager (V2.0; Open Imaging) as previously described [89,90]. The camera lens (Xenon 25 mm f/0.95; Schneider, Germany) was modified with a 5-mm optical spacer (Cosmicar, Japan) to increase the focal length and decrease the working distance.…”
Section: Luciferase Imagingmentioning
confidence: 99%
“…The extent of temperature compensation has been shown to vary between Arabidopsis accessions (Gould et al, 2006; Kusakina, Gould, & Hall, 2014). Rhythm robustness is also strongly affected by temperature, although the temperature which produces the most rhythmic oscillations appears to be dependent on the species and circadian assay used (Kusakina et al, 2014; Rees et al, 2019). Plants with clocks which resonate with environmental conditions are typically fittest, however it has been suggested that in climates with large seasonality there may be a compromise for clocks which are adaptable to rapidly changing day‐lengths (Michael et al, 2003).…”
Section: Introductionmentioning
confidence: 99%